Can Work-Life Balance Play a Role as A Moderating Variable in The Influence of Organizational Citizenship Behavior on Employee Performance? - Roy Rocky Suprapto Baan; Adrian Polim; M. Pahlan; Dirhamsyah; Eddi Suprayitno (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This study aims to empirically examine the moderating role of Work-Life Balance (WLB) in the relationship between Organizational Citizenship Behavior (OCB) and Employee Performance within the high-pressure corporate environment of 2026. While OCB is traditionally viewed as a positive contributor to organizational efficiency, the extra-role efforts involved may lead to employee burnout if not balanced with personal well-being. Using a quantitative research design and Moderated Regression Analysis (MRA), this study analyzes data from diverse professional sectors to determine whether the positive impact of OCB on performance is amplified or diminished by the level of WLB an employee perceives. Preliminary conceptual analysis suggests that WLB is a crucial boundary condition: when WLB is high, employees' voluntary contributions (OCB) translate more effectively into sustainable performance. Conversely, in the absence of WLB, excessive OCB may lead to "citizenship fatigue," ultimately hindering long-term productivity. This research contributes to human resource management literature by integrating social exchange theory and the conservation of resources theory to explain the complex synergy between voluntary work behavior and personal life harmony.